Epigenetic Therapy Ties MYC Depletion to Reversing Immune Evasion and Treating Lung Cancer - Topper, Michael J.; Vaz, Michelle; Chiappinelli, Katherine B.; Shields, Christina E. Destefano; Niknafs, Noushin; Yen, Ray-Whay Chiu; Wenzel, Alyssa; Hicks, Jessica; Ballew, Matthew; Stone, Meredith; Tran, Phuoc T.; Zahnow, Cynthia A.; et al. (Cell, 2017)
Combining DNA-demethylating agents (DNA methyltransferase inhibitors [DNMTis]) with histone deacetylase inhibitors (HDACis) holds promise for enhancing cancer immune therapy. Herein, pharmacologic and isoform specificity of HDACis are investigated to guide their addition to a DNMTi, thus devising a new, low-dose, sequential regimen that imparts a robust anti-tumor effect for non-small-cell lung cancer (NSCLC). Using in-vitro-treated NSCLC cell lines, we elucidate an interferon α/β-based transcriptional program with accompanying upregulation of antigen presentation machinery, mediated in part through double-stranded RNA (dsRNA) induction. This is accompanied by suppression of MYC signaling and an increase in the T cell chemoattractant CCL5. Use of this combination treatment schema in mouse models of NSCLC reverses tumor immune evasion and modulates T cell exhaustion state towards memory and effector T cell phenotypes. Key correlative science metrics emerge for an upcoming clinical trial, testing enhancement of immune checkpoint therapy for NSCLC.
EVALuna2:36340